2017
DOI: 10.1111/1755-5922.12266
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine vs metoprolol in patients with acute inferior wall myocardial infarction—“Expanding arena for ivabradine”

Abstract: Ivabradine is well tolerated and equally effective as metoprolol in acute inferior wall ST elevation myocardial infarction patients for lowering the heart rate with lesser risk of AV blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Therefore, existing guidelines for STEMI have given Class-I recommendation to oral beta-blockers therapy administration promptly to patients without contraindications. Betablockers have the propensity to cause AV block and there is a 19% incidence of high degree heart block complicating acute inferior infarction [16]. However, the use of beta-blockers is restricted in some patient's subgroups with severe LV dysfunction and acute bronchospasm or having cardiac conduction abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, existing guidelines for STEMI have given Class-I recommendation to oral beta-blockers therapy administration promptly to patients without contraindications. Betablockers have the propensity to cause AV block and there is a 19% incidence of high degree heart block complicating acute inferior infarction [16]. However, the use of beta-blockers is restricted in some patient's subgroups with severe LV dysfunction and acute bronchospasm or having cardiac conduction abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Betablockers are the most regularly used first-line therapy. The use of β-blockers is complex and controversial in patients with conduction abnormalities, severe LV dysfunction and active bronchospasm, severe airway obstruction, chronic fatigue, cardiogenic shock, hypersensitive to β-blockers, severe hypertension, peripheral vascular disease, patient on ventilator, persistent tachycardia, and post-operative persistent tachycardia [16]. Ivabradine quite the reverse to beta-blockers has been shown better myocardial perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two trials reported the incidence of MACE, 31,40 and an additional trial reported the incidence of a composite outcome 37 of death and cardiovascular endpoints (for details regarding the definitions of MACE in each trial, please refer to the online Supplementary material) in ivabradine and control groups. One trial reported the incidence of MACE in the whole cohort only, and data could not be analysed 35 (the authors were contacted, but no answer was obtained).…”
Section: Primary Endpointsmentioning
confidence: 99%
“…Six trials reported data on the incidence of new or worsening heart failure. 32,34,36,37,40,41 There were 23 (3.8%) events in the ivabradine group and 35 (6.1%) in the control group with no evidence of a difference between groups (six RCTs, n¼1177; OR¼0.59; 95% CI, 0.23e1.50; P¼0.27) ( Supplementary Fig. S3a).…”
Section: New or Worsening Heart Failurementioning
confidence: 99%